2010
DOI: 10.1007/s11356-010-0418-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of dioxin-like contamination in soil and sediments from the “hot spot” area of petrochemical plant in Pancevo (Serbia)

Abstract: This study demonstrates the utility of combined application of bioassays and instrumental analysis, especially for developing and transition country which do not have capacity of the expensive instrumental analysis. The results indicate the high contamination of soil in the area of petrochemical plant, and PCDD/Fs contamination of the sediment from the waste water channel originating from the ethylene dichloride production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Therefore, it is most likely that petrochemical plants were responsible for the PCBs pollution since these compounds were widely used as insulating or lubricating oils in plastic, resin and rubber industry. In previous studies, high concentrations of PCBs had already been observed in the soil around petrochemical industrial plants (Kaisarevic et al, 2011;Nadal et al, 2007).…”
Section: Pcbsmentioning
confidence: 84%
“…Therefore, it is most likely that petrochemical plants were responsible for the PCBs pollution since these compounds were widely used as insulating or lubricating oils in plastic, resin and rubber industry. In previous studies, high concentrations of PCBs had already been observed in the soil around petrochemical industrial plants (Kaisarevic et al, 2011;Nadal et al, 2007).…”
Section: Pcbsmentioning
confidence: 84%
“…13,19,20 Previous studies have assessed the environmental risks posed by PCBs, PCDD/PCDFs and/or PAHs by use of instrumental analysis and/or in vitro bioassay. 2,7,8,13,18,21,23,[34][35][36] Here, RePs values derived from the latest literature were reapplied to estimate and compare the TEQs for selected sediment samples reported previously (Table 4). The P TEQ PCB + TEQ PCDD/PCDF calculated by use of RePs were generally greater than those by use of WHO TEFs, indicating the underestimation of H4IIE-luc related TEQs associated with dioxin-like PCBs and PCDD/PCDFs using WHO TEFs.…”
Section: Sampling Sitementioning
confidence: 99%
“…PCBs, dioxins, polycyclic aromatic hydrocarbons etc.) by measuring luciferase activity under the control of the arylhydrocarbon receptor (AhR ) [19] . In parallel, at the University of Frankfurt/Main agonistic activity at the aryl-hydrocarbon receptor is examined with a yeastbased bioassay [20].…”
Section: Dioxin-like Toxicitymentioning
confidence: 99%